AtxA-Controlled Small RNAs of Bacillus anthracis Virulence Plasmid pXO1 Regulate Gene Expression in trans - Corsi, Ileana D.; Dutta, Soumita; van Hoof, Ambro; Koehler, Theresa M. (Frontiers in Microbiology, 2021)
Small regulatory RNAs (sRNAs) are short transcripts that base-pair to mRNA targets or interact with regulatory proteins. sRNA function has been studied extensively in Gram-negative bacteria; comparatively less is known about sRNAs in Firmicutes. Here we investigate two sRNAs encoded by virulence plasmid pXO1 of Bacillus anthracis, the causative agent of anthrax. The sRNAs, named “XrrA and XrrB” (for p¬XO1-encoded regulatory RNA) are abundant and highly stable primary transcripts, whose expression is dependent upon AtxA, the master virulence regulator of B. anthracis. sRNA levels are highest during culture conditions that promote AtxA expression and activity, and sRNA levels are unaltered in Hfq RNA chaperone null-mutants. Comparison of the transcriptome of a virulent Ames-derived strain to the transcriptome of isogenic sRNA-null mutants revealed multiple 4.0- to >100-fold differences in gene expression. Most regulatory effects were associated with XrrA, although regulation of some transcripts suggests functional overlap between the XrrA and XrrB. Many sRNA-regulated targets were chromosome genes associated with branched-chain amino acid metabolism, proteolysis, and transmembrane transport. Finally, in a mouse model for systemic anthrax, the lungs and livers of animals infected with xrrA-null mutants had a small reduction in bacterial burden, suggesting a role for XrrA in B. anthracis pathogenesis.